Kansas Land Prices and Cash Rental Rates - Langemeier, Larry N. (My University, 1998)
This farm management guide reports Kansas land prices and cash rental rates for the period of 1979-1997. The data is meant to be useful to farm managers.
MF1100_1998_10
Keywords: MF1100; Economics; MF